Sunk cost fallacy : an experimental study on the effects of casino levy on gambling behaviour - Hoe, Zixiang (2012)
The Singapore government lifted the casino ban on 18th April 2005 and allowed the building of two casinos in the form of integrated resorts to attract tourism dollars to the nation state. The casino levy was used as a measure to impose a cost on local residents such that they would not frequent the casinos so as to mitigate the potential problems that could be brought about from the casinos.